Oral Verruciform Xanthoma within Lichen Planus: A Case Report and Literature Review - Vasileios I. Theofilou; Alexandra Sklavounou; Prokopios P. Argyris; Evanthia Chrysomali (Case Reports in Dentistry)
Background. Verruciform xanthoma is an uncommon benign tumor, which exhibits a wide range of clinical patterns. The occurrence of the lesion in patients with immune-mediated mucocutaneous diseases may suggest a role of localized epithelial cell damage and chronic inflammation in its pathogenesis. Case Report. A case of verruciform xanthoma on the tongue of a 56-year-old female with oral lichen planus is reported. An asymptomatic pink-white lesion with a granular surface was observed in the left lateral lingual border, which was closely associated with a white plaque and striae. An incisional biopsy was performed, and histologically, epithelial projections in a verrucous pattern were observed. In the subepithelial connective tissue, aggregates of foamy cells that exhibited immunoreactivity for CD68 were noted. The final diagnosis was verruciform xanthoma. The mucosa adjacent to the lesion demonstrated histopathological features consistent with lichen planus. Conclusions. A total of twelve cases of oral verruciform xanthomas in patients with oral lichen planus including the present case have been reported in the literature. The clinician should be aware that verruciform xanthoma may mimic malignancy, and therefore, biopsy is required for definitive diagnosis to be established, especially when this tumor develops within conditions that show potential for malignant transformation.